The Influence Of Coffee Export Price And Japan’s Percapita Income On The Central Java’s Coffee Export Volume To Japan - Arlinta Nur Rahmawati; Yuli - Sudarsa; Nur - Rini (Politeknik Negeri Semarang, 2020)
The aim of this study is to examine the influence of coffee export prices and Japan’s percapita income on the Central Java’s coffee export volume to Japan partially and simultaneously. The secondary data are coffee export price and Central Java’s coffee export volume in annual periods from 2002 to 2017 taken from the Central Java Statistics Agency and Japan’s percapita income taken from The World Bank. Multiple linear regression test is applied to observe the influence. It is found that, export price have a significant and negative effect on the volume of Central Java’s Coffee Exports to Japan with coefficient value of -1.133 which means that every one dollar increase of coffee export price will reduce the volume of Central Java coffee exports to Japan by 1.133 tons. Meanwhile, Japan's percapita income has a significant and positive influence with coefficient value of 0.620 which means that every one dollar increase of Japan's per capita income will increase the volume of Central Java’s coffee exports to Japan by 0.620 tons. Both variables simultaneously influence 66.4 percent on the volume of Central Java’s coffee exports to Japan